Chemotaxis and degradation of organophosphate compound by a novel moderately thermo-halo tolerant Pseudomonas sp. strain BUR11: evidence for possible existence of two pathways for degradation - Pailan, Santanu; Saha, Pradipta (PeerJ, 2015)
An organophosphate (OP) degrading chemotactic bacterial strain BUR11 isolated from an agricultural field was identified as a member of Pseudomonas genus on the basis of its 16S rRNA gene sequence. The strain could utilize parathion, chlorpyrifos and their major hydrolytic intermediates as sole source of carbon for its growth and exhibited positive chemotactic response towards most of them. Optimum concentration of parathion for its growth was recorded to be 200 ppm and 62% of which was degraded within 96 h at 37 °C. Growth studies indicated the strain to be moderately thermo-halo tolerant in nature. Investigation based on identification of intermediates of parathion degradation by thin layer chromatography (TLC), high performance liquid chromatography (HPLC), gas chromatography (GC) and liquid chromatography mass spectrometry (LC-MS/MS) provided evidence for possible existence of two pathways. The first pathway proceeds via 4-nitrophenol (4-NP) while the second proceeds through formation of 4-aminoparathion (4-APar), 4-aminophenol (4-AP) and parabenzoquinone (PBQ). This is the first report of chemotaxis towards organophosphate compound by a thermo-halo tolerant bacterium.
Keywords: Organophosphate insecticide; Parathion; Chemotaxis; 16S rRNA gene; Degradation